LAMBOYA PHONOLOGY - DJAWA, ALEX; NURHUDA, ARIS (Postgraduate School, Universitas Nusa Cendana, 2023)
Based on research results and studying of the phonology of the Lamboya language, it is found five forms of vowel phonemes. The five vowel phonemes are in complete distribution. That is, all vowel sounds are found at the beginning, middle and end of a word. In BL found sixteen consonant phonemes which are not completely distributed. Two sounds, namely /j and ny/ are not found at the beginning and end of a word, only found in the middle of a word. BL is vocalist's language. Meanwhile, all consonant sounds are not found at the end of the word. Therefore, it can be stated that BL is the vocalist's language.